Raising the case of hepatitis E: report from the 2nd international HEV symposium : short communication - Kang, Sophie; Chung, Eun; Hong, Chloe; Aziz, Asma Binte; Kirkwood, Carl D.; Marks, Florian (Vaccine, 2024)
The 2nd International Hepatitis E Virus Symposium was held on April 28 and 29, 2023, in London, UK. The conference was hosted by the International Vaccine Institute and brought together key clinicians, researchers, and private and public stakeholders for a dedicated forum on hepatitis E virus (HEV). The scientific program spanned multiple facets of HEV, from updates on clinical research and diagnostic advances to vaccine development. The conference highlighted presentations on several critical HEV vaccine studies that will greatly impact the field, including the largest effectiveness study of Hecolin vaccine outside of China and the first reactive mass-vaccination campaign in South Sudan. This report summarizes information shared at the convening and offers perspectives on the steps forward for hepatitis E.